Evaluation of a Loop-Mediated Isothermal Amplification Assay to Detect Carbapenemases Directly From Bronchoalveolar Lavage Fluid Spiked With Acinetobacter spp. - Moreno-Morales, Javier; Vergara, Andrea; Kostyanev, Tomislav; Rodriguez-Baño, Jesús; Goossens, Herman; Vila, Jordi (Frontiers in Microbiology, 2021)
Carbapenem-resistant Acinetobacter spp. mainly Acinetobacter baumannii are frequently causing nosocomial infections with high mortality. In this study, the efficacy of the Eazyplex® SuperBug Complete A system, based on loop-mediated isothermal amplification (LAMP), to detect the presence of carbapenemases in Acinetobacter spp. directly from bronchoalveolar lavage samples was assessed. A total of 22 Acinetobacter spp. strains producing OXA-23, OXA-40, OXA-58, NDM and IMP were selected. Eazyplex® SuperBug Complete A kit, used with the Genie II device, is a molecular diagnostics kit that detects a selection of genes which express carbapenemases (blaKPC, blaNDM, blaVIM, blaOXA-48, blaOXA-23, blaOXA-40 and blaOXA-58). Negative BAL samples were identified, McFarland solutions were prepared from each of the 22 Acinetobacter strains and serial dilutions in saline solution were made to finally spike BAL samples to a concentration of 102 and 103 CFU/ml. 10 concentrations out of the 38 tested out did not provide detection of the carbapenemase producing gene, all but one being at the lowest concentration tested at 102 CFU/ml, therefore, the limit of sensitivity is 103 CFU/ml. This assay represents the kind of advantages that investing in molecular diagnostics brings to the clinical practice, allowing the identification of carbapenemases in less than 30 minutes with a sensitivity of 103 CFU/ml.